Organizational culture transformation model: Towards a high performance organization - Asier Ipinazar; Enara Zarrabeitia; Rosa Maria Rio Belver; Itziar Martinez-de-Alegría (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The main objective of this research is to design an Organizational Culture Transformation Model (OCTM) prototype, in order to enable a High Performance Organization (HPO). Design/methodology/approach: There are three main processes involved in the methodology. Two of them, the definition of the main OCTM work elements as an initial hypothesis based on a work environment approach and the scientific visualization of the key Organizational Culture research hubs through the analysis of the main topics in research publications, flow in parallel. Subsequently, at a certain point, both of these merge in a third process, the OCTM prototype definition. This last process, will deliver the Organizational Culture Transformation Model prototype, which essentially constitutes the main objective of the study. Findings: As result of the methodology, an Organizational Culture Transformation Model prototype has been developed. Originality/value: The resulting model will serve as a reference framework for those companies that wish to conduct an in-depth re-structuring of their operations, focusing it on their human capital.
Keywords: 650; organizational culture; high performance organization; organizational culture transformation model; manufacturing industry